Hyperphosphatemic Familial Tumoral Calcinosis in Two Siblings with a Novel Mutation in GALNT3 Gene: Experience from Southern Turkey - Rabia Miray Kışla Ekinci; Fatih Gürbüz; Sibel Balcı; Atıl Bişgin; Mehmet Taştan; Bilgin Yüksel; Mustafa Yılmaz (Galenos Yayincilik, 2019)
Inactivating autosomal recessive mutations in fibroblast growth factor 23 (FGF23), klotho (KL) and polypeptide N-acetylgalactosaminotransferase 3 (GALNT3) genes lead to a rare disorder, hyperphosphatemic familial tumoral calcinosis (HFTC). Patients with HFTC present with hyperphosphatemia and tumor like soft tissue calcifications. Although 78% of patients develop their first symptoms between the ages of 2-13 years, diagnosis is usually delayed until adulthood. Some individuals with the same genetic defect develop a condition named hyperphosphatemic hyperostosis syndrome. Herein we report two siblings suffering from periarticular, warm, hard and tender subcutaneous masses. Subcutaneous calcifications were present on X-ray and biopsy results were consistent with calcinosis in both patients. Laboratory results showed marked hyperphosphatemia and elevated renal tubular phosphate reabsorption rates, normal renal function tests and normal serum 25-hydroxyvitamin D levels. Thus, we suspected HFTC and performed next generation sequencing for the GALNT3 gene, reported as the most frequent cause. A novel homozygote P85Rfs*6 (c.254_255delCT) mutation in GALNT3 was identified in both siblings. Our report adds two new patients to the literature about this rare genetic disease and suggests that small deletions in the GALNT3 gene may be related with HFTC phenotype.